(untitled) (Journal of the College of Basic Education, 2022)
The process of researching language is no longer a process that is isolated from the elements of the situation accompanying the production of discourse; The text is an object that I can describe as stagnant, but it is alive and moving when it is released by (the preacher) or the speaker. To be a speech that carries intended meanings and connotations to reach the addressee; The idea of ​​the research is based on subjecting the discourse of the Iraqi constitution in force to study according to the deliberative approach, given the capabilities and axes that this approach carries; Especially the study of (acts of speech) or (achievements) that make us stand on the most important ideas presented by the discourse and how to employ the language to serve the delivery of those ideas to the recipient, and then what the recipient must do, which is the target in the communication process, meaning that the accomplished action is the essence of the process conversational.